The Perils of Gadgets for Toddlers: An In-Depth Exploration of Potential Hazards on Physical, Cognitive, and Socio-Emotional Development - Graciano Joaquim (Global Writing Academica Researching and Publishing, 2023)
The widespread adoption of gadgets in modern society has significantly impacted the lives of people, including young children. This article aims to examine the potential hazards that gadgets pose to toddlers. Through a comprehensive review of existing literature, we explore the adverse effects of excessive gadget usage on various aspects of a toddler's physical, cognitive, and socio-emotional development. The findings underscore the importance of limiting gadget exposure in the early years and promoting healthier alternatives for optimal child development.